Role of cooperative HRD institutions in the emerging markets : Conference of the Principals of National Cooperative Training Institutions in Asia : summary & discussion papers, March 20-24, 1995 - Prathap Reddy, K. (Workshop report (Institute of Rural Management (Anand, India)), 1995)
Contributed articles.